Marine spatial planning makes room for offshore aquaculture in crowded coastal waters - S. E. Lester (Nature Portfolio, 2018)
Marine spatial planning is used to co-ordinate multiple ocean uses, and is frequently informed by tradeoffs and composite metrics. Here, Lester et al. introduce an approach that plans for multiple uses simultaneously whilst balancing individual objectives, using a case study of aquaculture development in California.